(untitled) (Journal of Philosophy Culture and Political Science, 2025)
This work considers the theme of Eastern epic tales and the tradition of nazira, its historical, philosophical and cultural aspects which left a significant mark in the culture and literature of the Great Steppe. This study analyzes retrospective aspects of Eastern motifs, as well as their main ideas and spiritual directions. The aim of the research is to determine philosophical concepts in Eastern works and to identify their evolution through the analysis of epic tales and nazira tradition, as well as to study their genesis from a philosophical-cultural perspective. The research methodology includes the use of philosophical conceptual approaches and methods of historical periodization. The work analyzes texts of literature books based in Kazakhstan, as well as studies its historical-comparative analysis and genetic approach. While studying the content of epic works, the main categories such as wisdom, justice, fortune, good and evil are revealed, often found in Eastern reflections. The process of synthesis and improvement of such categories as foreign and own is analyzed through the perception of nazira as a method. This article substantiates the philosophical significance of Eastern tales and dastans for modern society, reveals the ways of ancient mythological images transmitted in literary language and peculiar technologies of their adaptation in other languages. Considering nazira tradition as a special company, conclusions presented by the author reveal its peculiar nature and functions. The study shows that the genesis of this tradition appear not only in literary tradition but also in the spiritual culture of society, art and social myths, as well as in the development of science including natural and humanitarian field. In conclusion, the author notes peculiar features of nazira tradition, considering recurring elements of human spiritual culture presented in various formats. Keywords: nazira, myth, national identity, literature, translation, language.